Thrombotic events in patients with antiplatelet factor 4/heparin antibodies. Issue 16 (28th May 2009) - Mattioli, A V; Bonetti, L; Carletti, U; Ambrosio, G; Mattioli, G
Abstract : Background: Antibodies to the heparin/platelet factor 4 (PF4) complex are linked to the pathogenesis of heparin-induced thrombocytopenia type II, and to the thrombotic complications associated with this syndrome. We investigated the long-term relation between antibody concentration and thrombosis. Methods: 250 patients who had been treated with unfractionated heparin as part of cardiac surgery management were included in the study. The immunoassay ELISA test was used to detect the presence and the plasma concentration of heparin/PF4 antibodies (as optical density value, OD). Follow-up lasted one year and new thrombotic events (myocardial infarction, stroke, pulmonary embolism), and death from any cause, were evaluated. Results: 79 of 250 patients (31.6%) developed anti-PF4/heparin antibodies after cardiac surgery. Nadir platelet count was significantly lower in patients who developed antibody positivity (82 (31)/10 9 vs 105 (52)/10 9, p<0.001). At follow-up, patients with anti-PF4/heparin antibodies were more likely to die or develop myocardial infarction (25.3% vs 10.5%, p<0.001), pulmonary embolism (20.2% versus 5.8%, p<0.001) or stroke (12.6% vs 5.8%, p<0.001), than patients who were antibody-negative. Patients were categorised in quintiles of antibody concentration according to the OD. The risk of developing thrombotic events markedly increased with increasing quintile of OD, with the highest group showing an odds ratio of 7.68 (95% CI 4.04 to 9.20) (p<0.001). Conclusions: Patients who develop antibodies to the PF4/heparin complex have a significantly higher rate of thrombotic events during a one-year follow-up than those who lack these antibodies; within this group the risk of developing thrombosis increases with increasing plasma concentration of antibodies.